Pengetahuan kesehatan gigi dan mulut di masa pandemi pada siswa sma di manado - Arvando Johannis, Christopher; Asia, Asyurati (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Background: During a pandemic, dental and oral hygiene is often neglected. Lack of knowledge will give rise to new problems related to dental and oral hygiene. Knowledge about dental and oral health for the younger generation and the community is important to be maintained and improved during the pandemic. Objective: Defines an overview of youth student knowledge of oral health during an pandemic. Method: This is a descriptive observational study. Respondents filled out informed consent and questionnaires via Google Forms. This study was conducted by distributing a questionnaire containing 22 oral health questions to 114 adolescent students at Eben Haezer High School. Respondents filled out informed consent and questionnaires via Google Forms. Respondents were classified into good, satisfactory, and poor according to the results of answers to the questionnaire questions. Result: The outcomes of the studies records confirmed that the teenage students of SMA Eben Haezer Manado had poor knowledge (10.53%), sufficient knowledge (34.21%%), and good knowledge(55.26%). Conclusion: Most of the teenage students of Eben Haezer High School in Manado, have good dental and oral health knowledge (55.26%) during the pandemic